Morphology analysis of vertebral trabecular bone under dynamic loading based on multi-scale theory - Khairul Salleh, Basaruddin; Takano, Naoki; Yoshiwara, Yuto; Nakano, Takayoshi (Springer-Verlag, 2013)
Link to publisher's homepage at http://link.springer.com/